Concussions in international ice hockey championships and olympic winter games between 2006 and 2015. Issue 11 (25th May 2017) - Tuominen, Markku; Hänninen, Timo; Parkkari, Jari; Stuart, Michael J; Luoto, Teemu M; Kannus, Pekka; Aubry, Mark
Abstract : Objective: To describe the occurrence and trend of concussions during the international ice hockey tournaments. Design: Register study. Setting: The International Ice Hockey Federation (IIHF) World Championships (WC) and Olympic Winter Games (OWG). Participants: A total of 3293 games were played in the 169 tournaments by 1212 teams (26130 players) comprising 142244 athletic game exposures. Outcome measures: One hundred and sixty concussions were observed. Main results: The average injury rate (IR) for concussion was 1.1 per 1000 ice hockey player-games for all IIHF WC tournaments. The injury rate was highest in men's WC A-pool tournaments and OWG (IR 1.6) and lowest in women's WC and OWG (IR 0.9). However, the annual injury rate for concussion in men's tournament has been lower than that in World Junior tournaments since 2012. When a concussion occurred with contact on a flexible board the IR was 0.2 per 1, 000 player games while the number was 1.1 if the board and glass were traditional [RR for the latter: 6.4 (95% CI 1.50 – 27.61]. In men's tournaments, the trend of concussions caused by illegal hits decreased over the study period. After the 2012 Zurich Consensus Guidelines none of the concussed players in men's WC returned to play during the same day. Conclusions: The risk of concussion was significantly lower if games were played on rinks with flexible board and glass. Between 2006 and 2015, the annual risk of concussion in men's WC has been decreasing because of the decreasing number of concussions caused by illegal hits. Competing interests: None